2015
DOI: 10.18203/issn.2454-5929.ijohns20150583
|View full text |Cite
|
Sign up to set email alerts
|

A case series of superficial parotidectomy under local anesthesia

Abstract: Superficial parotidectomy is the biopsy procedure of choice for all parotid neoplasm's as well as therapeutic choice for small low-grade malignancies. The key to successful parotid surgery is identification of the facial nerve. It is usually done under general anesthesia (GA).The main focus in this procedure is to remove entire superficial parotid gland along with a disease and at the same time preventing any iatrogenic injury to facial nerve and its peripheral branches which supplies over the face. We present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…These authors did not have any cases of conversion to general anesthesia, and 2 patients exhibited postoperative facial nerve paresia but recovered completely. Finally, in 2015, Singh et al reported on 3 patients with high anesthetic risks for whom continuous anesthesia with catheters located at the maxillary and mandibular nerves was administered; these authors achieved good outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These authors did not have any cases of conversion to general anesthesia, and 2 patients exhibited postoperative facial nerve paresia but recovered completely. Finally, in 2015, Singh et al reported on 3 patients with high anesthetic risks for whom continuous anesthesia with catheters located at the maxillary and mandibular nerves was administered; these authors achieved good outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…By and large, this procedure is performed under general anesthesia, which facilitates facial nerve monitoring and allows for more meticulous dissection in the immobile, anesthetized subject. However, the majority of parotid tumors occur during the sixth and seventh decade of life [9], which increases the likelihood that accumulated medical comorbidities may present a very high risk of undergoing general anesthesia. Surgery remains the most effective treatment for salivary malignancies with improved cure rates by the addition of adjuvant radiotherapy for high grade carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of malignancy, surgical excision is key to achieving better locoregional control, disease-free survival, and overall survival compared to nonsurgical treatments such as radiation [1]. Parotidectomy under local anesthesia is a treatment option that has been reported in other countries for a wide variety of indications [2][3][4][5][6][7][8][9]. We report our series of six patients undergoing parotidectomy under local anesthesia, which is the largest series reported in the United States to date.…”
Section: Introductionmentioning
confidence: 99%
“…Local or regional anesthesia can be used to preserve facial nerve. Under LA, patient complaints of pain and discomfort if dissection involves facial nerve sheath or its peripheral branches thus helping in its identification and prevention of iatrogenic nerve injury [1].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical management is individualized due to wide variability in the clinical behavior and presentation and influenced by tumor location, histological grade, extent, and spread. The surgical management includes superficial parotidectomy, total conservative parotidectomy, and radical parotidectomy, palliative biopsy only, and neck dissection [1].…”
Section: Introductionmentioning
confidence: 99%